Procedure for lean production in industry: a case study applied to automotive industry - Oliveira, Caio Cesar; Mata-Lima, Herlander (Revista Hipótese, 2016)
This work evaluates the methodology and the potential benefits with projects related to Cleaner Production (P+L), developed by an automobilist company. We consider the whole process since the Project conception, the implantation as well as the results, looking forward a conclusive result concerning its environmental and socioeconomics advantages. To reach such results, implanted projects were analyzed in a company, located in the ABC region, looking forward a final balance of the socioeconomics and environmental aspects of the organization. This study contributes to present the real benefits of projects directed to sustainability, as well as point out examples of finished projects. The results allow us to conclude that Cleaner Production techniques provide not only environmental, but also socioeconomics benefits, with low investments.